Social media influence in the COVID-19 Pandemic - González-Padilla, Daniel A. (Int Braz J Urol, 2020)
Never before in human history has it been possible to communicate so quickly during a pandemic, social media platforms have been a key piece for the dissemination of information; however, there are multiple advantages and disadvantages that must be considered. Responsible use of these tools can help quickly disseminate important new information, relevant new scientific findings, share diagnostic, treatment, and followup protocols, as well as compare different approaches globally, removing geographic boundaries for the first time in history. In order to use these tools in a responsible and useful way, it is recommended to follow some basic guidelines when sharing information on social networks in the COVID-19 era. In this paper, we summarize the most relevant information on the influence, and advantages, and disadvantages of the use of social networks during the COVID-19 pandemic.